2017
DOI: 10.25011/cim.v40i1.28050
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells ameliorate nephrosis through repair of impaired podocytes

Abstract: Bone marrow-derived mesenchymal stem cells ameliorate nephrosis through repair of impaired podocytes Abstract Purpose: The purpose of this study was to investigate the effects of bone marrow-derived mesenchymal stem cells (BMSC) on podocytes of puromycin amino nuclear glucoside (PAN) -induced nephrosis in mice.Methods: Mice were randomly divided into Control, PAN and BMSC groups. Mice were injected with PAN (0.5 mg/g weight) via the tail vein. The 24-h urinary protein was obtained after modelling, and urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…It is well known that proteinuria is a biomarker for kidney dysfunction and an important prognostic factor for the progression of kidney disease 4 . Our results are in agreement with previous reports that mSC administration results in decreased protein excretion in the 5/6 nephrectomy model 15 and in the anti-Thy glomerulonephritis 1.1 model 21 , as well as in mice receiving one single dose of PAN, demonstrating a protective role of CTm in the reduction of proteinuria 22 . On the other hand, mSC administration in the adriamycin-induced nephropathy model did not modify the proteinuria 16,17 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that proteinuria is a biomarker for kidney dysfunction and an important prognostic factor for the progression of kidney disease 4 . Our results are in agreement with previous reports that mSC administration results in decreased protein excretion in the 5/6 nephrectomy model 15 and in the anti-Thy glomerulonephritis 1.1 model 21 , as well as in mice receiving one single dose of PAN, demonstrating a protective role of CTm in the reduction of proteinuria 22 . On the other hand, mSC administration in the adriamycin-induced nephropathy model did not modify the proteinuria 16,17 .…”
Section: Discussionsupporting
confidence: 93%
“…While the induction of podocyte injury led to significant alterations in molecular composition, characterized by decreased WT1 expression and the downregulation of nephrin, podocin, synaptopodin, and podocalyxin expression, the administration of mSC in this disease model has shown a protective role by inducing a significant upregulation of WT1 and partial recovery of nephrin, synaptopodin, podocin, and podocalyxin expression. Our data confirm previous findings regarding the protective effect of mSC on podocytes 17,22,23 .…”
Section: Discussionsupporting
confidence: 93%
“…TRAF6 is specifically required for JNK and p38 signaling activation in a Smad-independent way. Other researchers found that the upregulation of TRAF6 in the peripheral blood of LN patients increased the possibility of ESRD progression and recurrence within 1 year ( Chen et al, 2017 ). In this study, the expression of p-Smad3 in the renal tissue was significantly increased in the LN model group but significantly inhibited in the UC-MSC + MP group.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of BMSCs, the expression of nephrin, CD2AP, and synaptopodin was up-regulated, while TRPC6 was down-regulated. Administration of BMSCs reduced excretion of protein through urine and protected podocytes from deleterious effects of PAN 10 . In a novel study, BM-MSCs along with human umbilical cord extract were used to enhance the proliferative capability of BM-MSCs against DN.…”
Section: Mesenchymal Stem Cells For Diabetic Nephropathymentioning
confidence: 98%